Identification of Phosphatin, a Drug Alleviating Phosphate Starvation Responses in Arabidopsis. Issue 3 (10th September 2014) - Arnaud, Carole; Clément, Mathilde; Thibaud, Marie-Christine; Javot, Hélène; Chiarenza, Serge; Delannoy, Etienne; Revol, Julia; Soreau, Paul; Balzergue, Sandrine; Block, Maryse A.; Maréchal, Eric; Desnos, Thierry; et al.
Abstract : A family of drugs reduces the growth response, the lipid modifications, and the pattern of gene expression triggered by inorganic phosphate starvation . Abstract: Inorganic phosphate (Pi ) is present in most soils at suboptimal concentrations, strongly limiting plant development. Plants have the ability to sense and adapt to the surrounding ionic environment, and several genes involved in the response to Pi starvation have been identified. However, a global understanding of the regulatory mechanisms involved in this process is still elusive. Here, we have initiated a chemical genetics approach and isolated compounds that inhibit the response to Pi starvation in Arabidopsis ( Arabidopsis thaliana ). Molecules were screened for their ability to inhibit the expression of a Pi starvation marker gene (the high-affinity Pi transporter PHT1;4 ). A drug family named Phosphatin (PTN; Pi starvation inhibitor), whose members act as partial suppressors of Pi starvation responses, was thus identified. PTN addition also reduced various traits of Pi starvation, such as phospholipid/glycolipid conversion, and the accumulation of starch and anthocyanins. A transcriptomic assay revealed a broad impact of PTN on the expression of many genes regulated by low Pi availability. Despite the reduced amount of Pi transporters and resulting reduced Pi uptake capacity, no reduction of Pi content was observed. In addition, PTN improved plant growth; this reveals that the developmental restrictions induced by Pi starvation are not a consequence of metabolic limitation but a result of genetic regulation. This highlights the existence of signal transduction pathway(s) that limit plant development under the Pi starvation condition.